Importance of Histopathological Grading for Treatment Selection in Malignant Mesothelioma - Türk, İlteriş; Findik, Gokturk; Çetin, Mehmet; Bicakcioglu, Pinar; Gülhan, Selim Şakir Erkmen; Aydoğdu, Koray; Yılmaz, Ülkü; Demirağ, Funda (The Thoracic and Cardiovascular Surgeon, 2023)
Background Complexities in TNM staging in epithelioid malignant pleural mesothelioma (MPM) may lead to errors in treatment selection, leading to major surgical interventions in patients with low survival expectations.Methods Sixty-nine stage I epithelioid MPM patients, including 27 patients treated with pleurectomy/decortication (P/D) and multimodal therapy (MMT) (the P/D [MMT] group), and 42 patients treated with chemotherapy or chemoradiotherapy (the CRT group), were included in the study. After an initial evaluation of overall survival, all patients were grouped in terms of histopathological parameters and treatment types, and then, a secondary survival evaluation was performed for the groups.Results Forty-one patients were male, the mean age was 61.8 years. The median survival time was 26 months in the P/D (MMT) group, and 19.6 months in the CRT group, but the difference was not statistically significant. After grouping according to pathological criteria, a median survival time of 32.4 ± 2.9 months in the P/D (MMT) group and 21.9 ± 3.2 months in the CRT group was obtained among patients with histopathological low-grade tumors. Among patients with high-grade tumors, the median survival time was 18.3 ± 2.6 months in the P/D (MMT) group and 17 ± 4.4 months in the CRT group. Among patients with low-grade tumors, the P/D (MMT) group had longer survival. Median survival times were similar among patients with high-grade tumors.Conclusion In epithelioid MPM, histopathological grading by video-assisted thoracic surgery pleural biopsy can prove accurate in selecting patients for P/D and MMT.
Keywords: malignant pleural mesothelioma; histopathological grading; nuclear grading system; pleuretomy/decortication